Constitutional Right to Vote for People with Mental Disorders (PMWD) with Case Study in Yogyakarta, Indonesia - Diastama Anggita Ramadhan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The right to vote as one of the constitutional rights is certainly in favor of all Indonesian citizens, includingthose who suffer mental disorders. The Constitutional Court through the Constitutional Court Verdict Number135/PUU-XIII/2015 has stated people with mental disorders, as long as their condition is not permanent,they can vote. However, this verdict has the potential to violate the constitutional rights of the citizen. Thisresearch location will be carried out in the Special Region of Yogyakarta where it is one of the provinceswith the largest mental disorder communities in Indonesia. This research uses a normative juridical methodand focusing on literature studies as its main sources. This research will conclude about the method usedby people with mental disorders to access their right to vote. Furthermore, it will also explain the extent towhich the Constitutional Court’s decision has an impact on patients with psychiatric disorders in the SpecialProvince of Yogyakarta.